2015
DOI: 10.1371/journal.pntd.0003447
|View full text |Cite
|
Sign up to set email alerts
|

Review on Dog Rabies Vaccination Coverage in Africa: A Question of Dog Accessibility or Cost Recovery?

Abstract: BackgroundRabies still poses a significant human health problem throughout most of Africa, where the majority of the human cases results from dog bites. Mass dog vaccination is considered to be the most effective method to prevent rabies in humans. Our objective was to systematically review research articles on dog rabies parenteral vaccination coverage in Africa in relation to dog accessibility and vaccination cost recovery arrangement (i.e.free of charge or owner charged).Methodology/Principal FindingsA syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 44 publications
10
86
2
1
Order By: Relevance
“…We found that only 20.6% of the respondents vaccinated their puppies against rabies before the age of 3 months. According to [41], Majority of canine population across Africa consists of puppies younger than 3 months. Our results showed that the respondents who had owned dogs for more than 10 years were more likely to exhibit positive attitude towards rabies than those who had kept dogs for fewer years.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only 20.6% of the respondents vaccinated their puppies against rabies before the age of 3 months. According to [41], Majority of canine population across Africa consists of puppies younger than 3 months. Our results showed that the respondents who had owned dogs for more than 10 years were more likely to exhibit positive attitude towards rabies than those who had kept dogs for fewer years.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, owner charged vaccination coverage is generally low though the percentage of dogs vaccinated under free of charge vaccination schemes is high [32]. According to the WHO recommendation [20], 70% of the dog population must be regularly vaccinated to control rabies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low rabies vaccination coverage were reported in Africa (Jibat et al, 2015) and different parts of Nigeria including Zaria (Dzikwi et al, 2011), Lagos (Hambolu et al, 2014) and Aba (Otolorin et al, 2014), suggesting high risk of rabies transmission in the country. The consumption of "bush meat" which refers to meat from wild animals is another risk factor associated with the transmission of NZDs especially those originating from wild animal reservoirs (Alexander et al, 2012).…”
Section: Risk Factors Associated With the Spread Of Neglected Zoonosementioning
confidence: 99%